The Interpretation and Performance Techniques of the Aria Der Hölle Rache Kocht in Mainem Herzen by Wolfgang Amadeus Mozart - Sidabutar, Regina Halmin; Manalu, Kartini; Nainggolan, David (Melayu Arts and Performance Journal, 2024)
This study aims to identify the interpretation techniques and elements of the aria Der Hölle Rache Kocht in Mainem Herzen by Wolfgang Amadeus Mozart and to apply the performance techniques appropriately. Using a descriptive qualitative approach, this research utilizes video observations on YouTube, literature studies, and documentation to explore various interpretation techniques. The analysis focuses on musical elements, including dynamics, timbre, tempo, and melismatic style. Vocal techniques examined include sound production (covering breathing, vocal cords, resonance, and articulation), intonation, vibrato, head voice, and coloratura technique. The results indicate that this aria demands a high level of technical skill from the singer, particularly in mastering fast tempo, precise intonation, and high register usage. In addition to advanced vocal techniques, presenting this aria requires physical and environmental preparation, such as room temperature regulation and hydration, to maintain sound quality. It was found that the ability to combine emotional expression with vocal technique is key to successfully performing this aria, renowned as one of the most challenging pieces in the opera repertoire.